2011
DOI: 10.1371/journal.pone.0028789
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism Is Essential for the Colonization of Streptococcus thermophilus in the Digestive Tract of Gnotobiotic Rats

Abstract: Streptococcus thermophilus is the archetype of lactose-adapted bacterium and so far, its sugar metabolism has been mainly investigated in vitro. The objective of this work was to study the impact of lactose and lactose permease on S. thermophilus physiology in the gastrointestinal tract (GIT) of gnotobiotic rats. We used rats mono-associated with LMD-9 strain and receiving 4.5% lactose. This model allowed the analysis of colonization curves of LMD-9, its metabolic profile, its production of lactate and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Similar results were obtained with other mono associated rats [20], [22]. On a molecular basis, it is also illustrated by the similar amounts of the cell cycle arrest protein p21 Cip1 and the proliferation marker cycline D2 between GF and BSL rats (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were obtained with other mono associated rats [20], [22]. On a molecular basis, it is also illustrated by the similar amounts of the cell cycle arrest protein p21 Cip1 and the proliferation marker cycline D2 between GF and BSL rats (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…salivarius 4.6, and L. fermentum 3.9.2 have been selected for their genetic equipment and their phenotypic attributes favorable to their survival in the gastrointestinal tract and their high potential for binding to the epithelial cells of the intestinal tract [8], [9]. Several studies have used a single species or a cocktail of bacteria for their probiotic potential on the host [31], [32]; however, only a few of them focused on the host response, particularly on the structural maturation of the epithelium that occurred in the presence of bacteria [20][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clear winner in the competition for glucose was S. thermophilus (see Table S8a in the supplemental material). Consistently, streptococci dominate the small intestinal microbiota through the efficient and rapid uptake of simple carbohydrates (39), and carbohydrate metabolism is essential for the colonization of the intestine by S. thermophilus (54). The losers included L. lactis and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…A number of works indicate that utilization of glucose, lactose and fructose by S. thermophilus is a common characteristic in all existing studies, while galactose, mannose, sucrose, maltose, melibiose, and raffinose utilizations have variable profiles [40,41,42,43,44,45,46,47]. At the same time, it has been found that carbohydrate metabolism is essential for the colonization of S. thermophilus in the digestive tract of gnotobiotic rats [48]. Colonization ability is an important determining factor for developing bacterial health function in humans.…”
Section: Technological and Functional Properties Of S Thermophilusmentioning
confidence: 99%